THE IMPACT OF CAPITALIST SOCIETY ON ARTHUR’S CHARACTER DEVELOPMENT AS PORTRAYED IN JOKER (2019) FILM - Chairani, Muhammad Atthariq; Zamruddin, Mardliya Pratiwi; Max, Jonathan Irene Dewi Sartika (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
The purpose of this research is to find the impact of capitalist society on Arthur’s character development as seen in Joker film by using Karl Marx’s idea about marxism and characterization in film theory by Boggs and Petrie. Further, the research method used in this study was qualitative research with a marxism approach. The researcher also designed this research as a film study by using Mikos’s data analysis in film theory to conduct research. In this film, the researcher finds two social conditions that appeared as common features in capitalist society. The two aspects of capitalist society in the film are class distinction and human exploitation. The class distinctions in this film are divided into the bourgeoisie and the proletariat. In this case, only Arthur’s character in this film is shown to face many exploitations due to different classes. As a result, these social conditions in capitalist society influenced Arthur Fleck as the main character. As a dynamic character, it is shown how Arthur developed from a patient, caring, and kind-hearted person into an impulsive, reckless, and psychopathic person. These character developments are portrayed by Arthur’s external actions dialogues, and appearance.